HEALTH-RELATED QUALITY OF LIFE IN THAI CHILDREN WITH THALASSEMIA AS EVALUATED BY PEDSQL AND EQ-5D-Y: A SINGLE CENTER EXPERIENCE - Pacharapan Surapolchai; Phakatip Sinlapamongkolkul (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Thalassemia remains a chronic challenging disease in Thailand, but national prenatal screening along with better treatment and management may have improved health-related quality of life (HRQoL) for pediatric patients. We aimed to measure the HRQoL of transfusion dependent (TDT) and non-transfusion dependent (NTDT) of these pediatric patients at our institute.